A Raman spectroscopic study of teeth affected with molar–incisor hypomineralisation. (16th January 2015) - Fraser, Sara J.; Natarajan, Arun K.; Clark, Austina S. S.; Drummond, Bernadette K.; Gordon, Keith C.
<x xml:space="preserve">Abstract</x> Raman spectroscopy was used to chemically map lesions associated with molar–incisor hypomineralisation in human teeth. Three teeth with hypomineralised lesions of differing severity, described as white, yellow or brown, were mapped using integral ratios of major component bands (hydroxyapatite, amide I and b‐type carbonate) and principal component analysis scores values. These lesions were found to contain depleted levels of mineral (hydroxyapatite) compared with those of healthy enamel. Principal component analysis also highlighted changes in the phosphate structure and variations in various organic constituents. These variations were consistent with increased disorder in the mineral component of the hypomineralised tooth lesions. Scanning electron microscopy–energy dispersive X‐ray spectroscopy supported the findings based on Raman spectroscopy. Copyright © 2015 John Wiley & Sons, Ltd.